TECHNIFIED OBSERVATIONS AND COMPARABILITY IN SCIENCES (Andamios, Revista de Investigación Social, 2007)
In this paper, I criticize the notion of incommensurability between scientific theories proposed by Kuhn and I put forward a form of comparability based on what I call technified observations as a way to avoid the problem of theory-laddenness produced by untranslatability between theories. I develop three criticisms to the notion of translation that underlies the kuhnian project and to the use of the term incommensurability to refer to this form of lack of isomorphism. I also suggest a way in which progress in science is possible. Finally, I point out some consequences this proposal has for the philosophy, history and sociology of science and for some issues in general epistemology.
Keywords: Comparability; Kuhn; incommensurability; translatability; theory-laddenness